Forensic Psychology / Crime, Justice, Law, Interventions - Beech Anthony; Davies Graham; The British Psychological Society (2018)
This book highlights the often sizeable gap between media myths surrounding forensic practice and reality. Preface, Introduction, The Causes of Crime, Psychological Approaches to Understanding Crime, Developmental and Psychological Theories of Offending, Psychopathy, Understanding Risk Factors for Offending: The Contributors of Neuroscience, Effects of Interpersonal Crime on Victims, Investigating Crime, Eyewitness Witnesses, Interviewing Suspects, Detecting Deception, Offender Profiling and Crime Linkage, Interpersonal Violence and Stalking, Terrorism, The Trial Process, Judicial Processes, Safeguarding Vulnerable Witnesses, Identifying Perpetrators, The Role of the Expert Witness, Dealing with Offenders, Crime and Punishment: What Works?, Risk Assessment and General Offender Behaviour Programme Delivery, Treating Dangerous Offenders, Interventions with Female Offenders, Interventions for Offenders with Intellectual Disabilities, Interventions with Mentally Disordered Offenders, The Rehabilitation of Offenders: Good Lives and Risk Reduction, Glossary, Index.